Pengujian Sistem Informasi Video Marketplace Shopee Live Berdasarkan Karakteristik Usability Pada Pengguna Aplikasi Shopee - Dirgantara Sajid Raihan; Miftah Andriansyah; Karmilasari Karmilasari (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The use of smartphones by people in Indonesia, almost 98% of smartphones are used to download e-commerce applications and one of them is Shopee with the number of daily active visitors on Shopee e-commerce in December 2021 reaching 33.27 users. So this study aims to test the Shopee Live marketplace video information system based on the usability characteristics of Shopee application users. The method used in this research is a quantitative method. In this study, the ISO 25010 method was used to test usability characteristics. Before weighting, researchers test the data using the Validity Test and Reliability Test methods to measure the data used by researchers can be said to be valid and real. The research results from the weight calculation show that the weights for sub-characteristics using the ISO 25010 method show that appropriateness recognition is 35.1%, learnability is 24.5%, operability is 16.4%, user error protection is 11.5%, user interface aesthetics by 7.9%, and accessibility by 4.6% so it can be seen that the highest weight is the appropriateness recognition sub-characteristic